Digital Capacity Building Strategy of Local Government in Palopo City - Aulia Ayu Utari; Bima Pratama (Asian Digital Governance Problems, 2026)
Purpose: This study aimed to analyze the digital capacity building strategy implemented by the local government of Palopo City and examine the influence of human resource digital competence, institutional support, and technological infrastructure readiness on digital governance implementation effectiveness. Subjects and Methods: The study employed a quantitative descriptive and explanatory design using a cross-sectional survey approach. Data were collected from 128 government employees involved in digital administrative activities through structured questionnaires and analyzed using descriptive statistics and multiple linear regression with SPSS Version 26. Results: The findings revealed that all independent variables significantly influenced digital governance effectiveness. Human resource digital competence emerged as the strongest predictor, followed by institutional support and technological infrastructure readiness. The regression model explained 64.2% of the variance in digital governance effectiveness. Challenges related to system integration and interdepartmental coordination remained evident despite positive organizational readiness. Conclusions: Effective digital governance requires integrated strategies combining employee digital competence, institutional commitment, and sustainable technological infrastructure development within local government institutions.